Heterologous production of 3-hydroxyvalerate in engineered Escherichia coli - Miscevic, D.; Srirangan, K.; Kilpatrick, S.; Chung, D. A.; Moo-Young, M; Chou, C. P. (Metabolic Engineering, 2020)
3-Hydroxyacids are a group of valuable fine chemicals with numerous applications, and 3-hydroxybutyrate (3-HB) represents the most common species with acetyl-CoA as a precursor. Due to the lack of propionyl-CoA in most, if not all, microorganisms, bio-based production of 3-hydroxyvalerate (3-HV), a longer-chain 3-hydroxyacid member with both acetyl-CoA and propionyl-CoA as two precursors, is often hindered by high costs associated with the supplementation of related carbon sources, such as propionate or valerate. Here, we report the derivation of engineered Escherichia coli strains for the production of 3-HV from unrelated cheap carbon sources, in particular glucose and glycerol. Activation of the sleeping beauty mutase (Sbm) pathway in E. coli enabled the intracellular formation of non-native propionyl-CoA. A selection of enzymes involved in 3-HV biosynthetic pathway from various microorganisms were explored for investigating their effects on 3-HV biosynthesis in E. coli. Glycerol outperformed glucose as the carbon source, and glycerol dissimilation for 3-HV biosynthesis was primarily mediated through the aerobic GlpK-GlpD route. To further enhance 3-HV production, we developed metabolic engineering strategies to redirect more dissimilated carbon flux from the tricarboxylic acid (TCA) cycle to the Sbm pathway, resulting in an enlarged intracellular pool of propionyl-CoA. Both the presence of succinate/succinyl-CoA and their interconversion step in the TCA cycle were identified to critically limit the carbon flux redirection into the Sbm pathway and, therefore, 3-HV biosynthesis. A selection of E. coli host TCA genes encoding enzymes near the succinate node were targeted for manipulation to evaluate the contribution of the three TCA routes (i.e. oxidative TCA cycle, reductive TCA branch, and glyoxylate shunt) to the redirected carbon flux into the Sbm pathway. Finally, the carbon flux redirection into the Sbm pathway was enhanced by simultaneously deregulating glyoxylate shunt and blocking the oxidative TCA cycle, significantly improving 3-HV biosynthesis. With the implementation of these biotechnological and bioprocessing strategies, our engineered E. coli strains can effectively produce 3-HV up to 3.71 g l-1 with a yield of 24.1% based on the consumed glycerol in shake-flask cultures.